Peningkatan Kemampuan Mengendalikan Halusinasi Pendengaran Melalui Teknik Distraksi Menghardik - winnellia fridina sandy rangkuti; Sudarto Sudarto; Susito Susito; Sarliana Zaini; Anisa Khairiyah (WASATHON Jurnal Pengabdian Masyarakat, 2024)
Mental disorders are a phenomenon that continues to experience a very significant increase, and every year in various parts of the world the number of people with mental disorders is increasing. It is estimated that the number of people with mental disorders in the world is approximately 450 million people, with an estimated 10% of adults, and 25% at a certain age someone is predicted to experience mental disorders, and 135 million of them experience hallucinations. The goals of this activity is to provide education about controlling auditory hallucinations through rebuke distraction techniques. The method of this activity is by conducting tests (pre test and post test), before and after counseling is carried out to assess the level of knowledge or understanding of the community about controlling auditory hallucinations through rebuking distraction techniques as an indicator of the success of a health promotion program. Counseling showed that there was an increase in public knowledge or understanding of auditory hallucinations, from 25 to 95 percent. Based on the results of this assessment, it is hoped that the public can better understand the control and be aware of auditory hallucinations.